Improving the Quality of Human Resources Through Islamic Boarding School-Based Knowledge-Sharing Management - Ahmad Nadif Sanafiri (Indonesian Journal of Business Analytics, 2024)
This research aims to explore the potential of knowledge-sharing management (KSM) in improving the quality of human resources (HR) at Nurul Jadid Islamic Boarding School. Through a qualitative approach, data will be collected from interviews, observations, and document analysis. The research will highlight the improvement of religious, academic, and soft skills competencies through knowledge-sharing practices in the Islamic Boarding School. In addition, this research will investigate the factors that influence the effectiveness of KSM in the Islamic Boarding School environment. It is expected that the results of the study can provide in-depth insights into the role of KSM in the development of Islamic Boarding School human resources, as well as provide recommendations for relevant parties to improve more effective KSM practices at Nurul Jadid Islamic Boarding School. Thus, this research is expected to make a positive contribution to the development of Islamic Boarding School as an educational institution that is oriented towards improving the quality of human resources holistically.